Histone Modifications: Potential Therapeutic Targets for Diabetic Retinopathy - Yao Lu; Yizheng Zhang; Jin Yao; Wen Bai; Keran Li (Biomolecules)
Diabetic retinopathy (DR) is a microvascular complication arising as a secondary effect of diabetes, with both genetic and environmental factors playing a significant role in its onset and progression. Epigenetics serves as the crucial link between these genetic and environmental influences. Among the various epigenetic mechanisms, histone modification stands out as a key regulatory process associated with the development of many diseases. Histone modifications primarily regulate cellular function by influencing gene expression. Modulating histone modifications, particularly through the regulation of enzymes involved in these processes, holds a promising therapeutic approach for managing diseases like DR. In this review, we explore the regulatory mechanisms of histone modification and its contribution to the pathogenesis of DR.